Der Einfluss nachhaltigkeitsbezogener Objektmerkmale auf den Wert von Immobilien - ein Beitrag zur Weiterentwicklung von Datenhaltung und Wertermittlungsverfahren - Jäger, Anjulie (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft, 2021)
This work starts with the real estate industry as an important field of action for sustainable development and examines the consideration of sustainability-relevant property characteristics in the valuation of real estate. Taking into account econometric methods, the willingness to pay and the understanding of sustainability in real estate as well as the increase in value of sustainable object attributes is analysed.